THE CONCEPT AND CLASSIFICATION OF THE ELECTORAL SYSTEM - Boltabaev Bakhtiyor Sabirjonovich (Western European Studies, 2025)
In this article, the concept of the electoral system is provided with the history of its emergence, the goals of the elections, the extensive and narrow concept, information on modern electoral systems, majolicist, proporial and mixed electronic and mixed electronic and mixed electronic and mixed elections.
Keywords: History of elections; the goal and objective of elections